Listy Józefa Czapskiego do Stanisława Lorentza - Kowalczykowa, Alina; Stanisz, Marek (Tematy i Konteksty, 2017)
In this text six Józef Czapski’s letters to Stanisław Lorentz are published from years 1958-1960 and 1978. These letters concern donating Czapski’s drawings and paintings to the National Museum. One of them includes the painter’s reflections on the subject of his drawing and its importance for him.